OPTIMALISASI PENDIDIKAN AGAMA ISLAM MELALUI PENERAPAN MODEL INTEGRATED LEARNING SEBAGAIUPAYA MEMBENTUK KEPRIBADIAN MUSLIM PADA SISWA DI MTS. NEGERI PALASAH KABUPATEN MAJALENGKA - Taziri, Yus Yusuf Zaen (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
Islamic religious education in schools has not played an optimalrole because it is more theoretical, fragmented or less related to othersubjects. the learning model is still conventional, which emphasizescognitive knowledge only, rather than the formation of attitudes(affective) and habituation (psycho-motoric). Then it is time for Islamicreligious education to apply appropriate learning models in order toshape the behavior and personality of students so that students havetrue Muslim personalities. One model of Islamic religious educationlearning that is considered capable of overcoming all these problems,including the integrated learning model.This study has objectives, namely: 1) to find out about Muslimpersonalities, 2) to examine the role of Islamic religious education inthe formation of student personality, 3) to examine how the process ofapplying the integrated learning model in Islamic religious educationlearning, 4) to determine student responses regarding the application ofthe integrated learning model in the learning of Islamic religiouseducation.This research is a qualitative research using classroom actionresearch (CAR), conducted at MTs. Negeri Palasah MajalengkaRegency with 35 VIII-5 grade subjects. the data analysis technique usesnon-statistical analysis techniques, namely in the form of descriptiveanalysis. In this regard, the authors make a hypothesis, namely: "theoptimization of Islamic religious education through the application ofan integrated learning model can shape the Muslim personality ofstudents in MTs. Negeri Palasah Majalengka Regency "